(untitled) (Applied Biological Research, 2018)
In Planta methods have been developed in several plant species to overcome the problems associated with their tissue culture-based transformation. In present study, a method for genetic transformation in okra (Abelmoschus esculentus) was established using in planta Agrobacterium-mediated genetic transformation. The embryos of imbibed seeds pricked from meristematic region of plumule were used as explants for transformation. Agrobacterium tumefaciens strain EHA105 was carrying cry1Ac gene against fruit and shoot borer, CaMV 35S as promoter and nptII as plant selectable marker gene. The putative transgenic plants were confirmed by amplifying transgene through polymerase chain